The Basics of Molecular Biology - Vologodskii, Alexander (Cham : Springer International Publishing : Imprint: Springer, 2023)
Accessible and comprehensive, this book describes the universal cellular nature of living organisms and is an indispensable tool for anyone in the sciences who wishes to get a quick overview of molecular biology. Individual chapters cover nucleic acids and proteins, genetic code and protein synthesis, the fidelity of transferring genetic information to the next generations, and the regulation of various processes inside the cells. Special attention is paid to new areas rising from modern DNA sequencing technologies which transform biology. The book also touches on developing areas, such as cures for cancer and CRISPR, which are important for medicine and the future of humankind. .
Introduction -- The major processes in the biological world -- Enzymes, conformational changes, energy, and molecular motors -- The cells -- Genome -- Regulation of gene expression and protein activity -- DNA replication, its fidelity, mutations, and repair -- Transduction of signals -- Multicellular organisms and their development -- Biological defense I. Protection from foreign nucleic acids -- Biological defense II. The immune system of vertebrates -- Pathogens -- Cancer -- Index.
Keywords: Molecular biology; Cytology; Genetics; Virology; Cancer; Enzymology; Molecular Biology; Cell Biology; Genetics; Virology; Cancer Biology; Enzymology